Acute Illness Protocol for Maple Syrup Urine Disease. Issue 1 (January 2018) - Rodan, Lance H.; Aldubayan, Saud H.; Berry, Gerard T.; Levy, Harvey L.
Abstract : Abstract: Inborn errors of metabolism (IEMs) are genetic disorders that disrupt enzyme activity, cellular transport, or energy production. They are individually rare but collectively have an incidence of 1:1000. Most patients with IEMs are followed up by a physician with expertise in biochemical genetics (metabolism), but may present outside this setting. Because IEMs can present acutely with life-threatening crises that require specific interventions, it is critical for the emergency medicine physician, pediatrician, internist, and critical care physician as well as the biochemical geneticist to have information on the initial assessment and management of patients with these disorders. Appropriate early care can be lifesaving. This protocol is not designed to replace the expert consultation of a biochemical geneticist, but rather to improve early care and increase the level of comfort of the acute care physician with initial management of maple syrup urine disease until specialty consultation is obtained.